Exploring strategies used by physiotherapy private practices in hosting student clinical placements - Roma Forbes; Alana Dinsdale; Ruth Dunwoodie; Stephen Birch; Sandy Brauer
_Introduction:_ Private practice clinical education experiences are important for workforce readiness of physiotherapy graduates, however there are limited opportunities to experience this setting during training. Furthermore, private practice is considered a valuable source of placements for education providers where shortages occur. Exploring the strategies used by physiotherapy private practice providers when hosting students may provide insight into how students can be integrated into practice whilst minimising disruption to staff, clients and service delivery. _Methods:_ A qualitative study with a general inductive thematic analytical approach was undertaken. Semi-structured interviews of ten physiotherapy private practice placement providers responsible for student placement provision were used to explore the strategies used to successfully integrate students into private practice settings. _Results:_ Four key themes emerged following data analysis; developing systems, student service provision, finding other ways to educate, and seeking support from the education provider. _Conclusion:_ This study is the first to explore the perspective of private practice placement providers regarding how students are successfully integrated into private practice settings where learning and service delivery can be maximised. Areas for further research are outlined.